2016
DOI: 10.1186/s12960-016-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability of staffing and staff mix across acute care units in Alberta, Canada

Abstract: BackgroundThe health workforce has a crucial position in healthcare, and effective distribution of the workforce is one of the critical areas for healthcare improvement. This requires a proper understanding of the allocation of healthcare providers including staffing levels and staffing variability within a healthcare system. High variability may imply significant differences in outcomes and greater opportunity to better distribute staffing and improve patient outcomes. The objective of this study was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In acute care and long-term care sectors, patients and their families/visitors typically have length of stays long enough to recognize changes in quality of care imposed by work environment conditions such as staffing shortages, heavy workloads and long wait times [5,17,21]. Despite, differences in the conditions of nurses' works environments across geographical areas [18][19][20], we did not find statistically significant differences in the prevalence of most types of workplace violence across geographical areas. That said, the raw prevalence for most types of workplace violence was slightly higher in rural areas.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In acute care and long-term care sectors, patients and their families/visitors typically have length of stays long enough to recognize changes in quality of care imposed by work environment conditions such as staffing shortages, heavy workloads and long wait times [5,17,21]. Despite, differences in the conditions of nurses' works environments across geographical areas [18][19][20], we did not find statistically significant differences in the prevalence of most types of workplace violence across geographical areas. That said, the raw prevalence for most types of workplace violence was slightly higher in rural areas.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study, for example, found associations between nurses' heavy workloads, patient/family complaints and violence escalation [5]. Other research has established differences in adequacy of nurse staffing and workload management between healthcare sectors (e.g., acute care, long-term care) [17] and geographical regions (e.g., urban, rural) [18][19][20]. Violence research with nurses, therefore, needs to consider the variety of contexts that may influence acts of violence against them.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these efforts, clear evidence-based guidelines on staffing levels are lacking, particularly in regard to skill mix (Brennan, Daly, & Jones, 2013;Sharma, Hastings, Suter, & Bloom, 2016). A recent systematic review (Myers, Pugh, & Twigg, 2018) that examined the importance of nurse skill mix on patient outcomes focussed specifically on stand-alone high acuity areas, meaning that findings from this review may not be easily transferrable to other care settings.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis published in 2007 for example (Kane, Shamliyan, Mueller, Duval, & Wilt, 2007), which analysed nurse staffing levels, focussed on the ratio of Registered Nurses (RNs) to patients and patient outcomes, but not on nurse skill mix. Despite these efforts, clear evidence-based guidelines on staffing levels are lacking, particularly in regard to skill mix (Brennan, Daly, & Jones, 2013;Sharma, Hastings, Suter, & Bloom, 2016). A recent systematic review (Myers, Pugh, & Twigg, 2018) that examined the importance of nurse skill mix on patient outcomes focussed specifically on stand-alone high acuity areas, meaning that findings from this review may not be easily transferrable to other care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing care is increasingly provided by a nursing team with providers who have varying levels of education and roles (Aiken et al, 2017;Sharma, Hastings, Suter, & Bloom, 2016). Within the nursing team, in addition to RNs, LPNs and HCAs have been increasingly employed in homecare, community care and long-term facilities (Arain, Deutschlander, Rostami, & Suter, 2016;Hewko et al, 2015;Huynh, Alderson, Nadon, & Kershaw-Rousseau, 2011).…”
Section: Introductionmentioning
confidence: 99%